(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Cerebral palsy (CP) is a chronic neurological condition caused by brain injury or abnormal brain development during the perinatal period. It is characterized by impairments in motor, speech, cognitive, and social functions. This article analyzes modern approaches to the rehabilitation of children with CP, identifies key organizational challenges, and proposes practical solutions. Particular attention is given to the current situation in Uzbekistan, where accessibility and quality of rehabilitation services remain pressing issues.